Removal of heavy metals from wastewater using reverse osmosis - Kapepula, Vercus Lumami; Luis, Patricia (Frontiers in Chemical Engineering, 2024)
This study presents an overview of and innovations in reverse osmosis (RO) membrane processes for rejecting charged metal ions in wastewater in relation to the main problems associated with purification methods. It also explains the emergence of nanomaterials and the different methods applied for RO membrane modification to improve performance. Membrane regeneration and retentate management are also considered. The study concludes with an economic feasibility study for the industrial scale-up of the methodology.